Surgical Reconstruction of Traumatic Pseudoaneurysm of Palmar Arch Caused by Blunt Trauma - Nikolaos Papatheodorou; Konstantinos Dimitriadis; Damianos Doukas; Christos Argyriou; George S. Georgiadis (Vascular Specialist International, 2022)
Although rare, pseudoaneurysms (PAs) of the palmar arch are mostly considered benign. However, they can cause severe complications if left untreated or misdiagnosed. There are a few data on traumatic PAs of the palmar arch, particularly those most commonly caused by penetrating hand injuries. However, PAs caused by blunt trauma are more insidious in onset, presenting as a painful pulsatile mass in the palmar area of the hand, and require prompt diagnosis and management to avoid catastrophic sequelae. Our case is the first study to describe a patient with traumatic PA of the palmar arch caused by blunt trauma that was treated with surgical reconstruction and venous bypass interposition.